Analisis Pemahaman Budaya Tiongkok dan Indonesia dalam Mengatasi Gegar Budaya pada Dunia Kerja - Wahyuni, Sri; Arifin, Yohan Yusuf (Universitas Al Azhar Indonesia, 2025)
The development of the era from time to time has a significant impact on the world economic sector. This is also experienced by Indonesia and China. In recent decades, the two countries have established harmonious diplomatic relations, one of which is international cooperation in the economic sector. The results of this cooperation have caused many foreign workers from China to come to Indonesia. Due to cultural differences, this often creates challenges in understanding and adapting, therefore culture shock always accompanies workers from China, causing communication barriers that lead to misunderstandings. The purpose of this study is to identify and find solutions to culture shock that occurs in Chinese workers. This study is a qualitative study with a focus on an in-depth understanding of the phenomenon of the problems that occur, discussing existing problems in more depth. From the results of the study, it was found that to overcome culture shock, foreign workers from China and Indonesia must learn to understand and adapt to each other, in this case Mandarin has an important role not only in bridging the process of cultural adaptation between foreign workers from China and local Indonesian workers but also as a means of understanding values and norms, overcoming differences in cultural backgrounds and strengthening relations between the two parties.Keywords – China, Culture, Culture Shock, Indonesia.